MENGKAJI PAKAIAN ADAT SUKU MINAHASA DI PROVINSI SULAWESI UTARA SEBAGAI MELESTARIKAN BUDAYA - Mohamad Rizal Triansah; Syairul Bahar, Tengku Sri Ramadonna, Imelda Suryati Maulani, Aulia Nabila Safitri, Farhan Abdurochim (CV. ADIBA AISHA AMIRA, 2025)
The traditional clothing of the Minahasa Tribe in North Sulawesi Province is an important symbol in preserving local culture. This study aims to explore the meaning and function of traditional clothing in the social and cultural context of the Minahasa community. The method used is qualitative with interview techniques and literature studies, which allows researchers to understand in depth how traditional clothing reflects the cultural identity and values of the community. One of the traditional clothes of the Minahasa Tribe is Kawasaran. The Kawasaran traditional clothing of the Minahasa tribe not only functions as traditional clothing, but is also a cultural heritage that is full of historical meaning, noble values, and identity that describes the Minahasa community. This clothing is not only a body cover but also describes spiritual values, position in society, and the spirit of love for the homeland that is passed down from previous generations.